mRNA ratios of AR to ESR1 and PGR distinguish breast cancer subtypes based on public datasets and experimental models - Diego Prieto; Milena Rondón-Lagos; Paola Cruz-Tapias; Andrés Rincón-Riveros; Wilson Rubiano; Jairo De la Peña; Elizabeth Vargas; Victoria E. Villegas; Nelson Rangel (Scientific Reports)
Abstract The role of the androgen receptor (AR) in breast cancer (BC) remains incompletely understood. Here, we conducted a meta-analysis of large-scale microarray transcriptomic datasets to evaluate whether the mRNA expression levels of the androgen receptor gene, relative to those of the estrogen receptor gene (AR/ESR1 ratio) and the progesterone receptor gene (AR/PGR ratio), can help differentiate BC tumor subtypes. Additionally, we used qRT-PCR assays to assess the mRNA levels of the AR/ESR1 and AR/PGR ratios in four cell lines representative of different BC subtypes (MCF7, BT474, MDA-MB453, and MDA-MB231), as well as in breast tissue from a small group of patients (11 cases) stratified by estrogen receptor (ER) status. Our results showed that higher AR gene expression relative to ESR1 and PGR (≥ 2.0 and ≥ 1.54, respectively) were associated with BC patients classified under the Luminal B and HER2-enriched subtypes. Positive values of AR/ESR1 and AR/PGR ratios were also observed in the ER-negative (ER-) cell line MDA-MB453, as well as in tumor tissue from ER- BC patients. Our findings confirm that higher or even positive AR/ESR1 and AR/PGR ratios may be associated with BC cases exhibiting more aggressive clinical and biological features, leading to a worse prognosis.